'Never such weather known in these seas': Climatic Fluctuations and the Anglo-Dutch Wars of the Seventeenth Century, 1652-1674. (1st May 2014) - Degroot, Dagomar
Abstract : In the North Sea region, the so-called Little Ice Age reached a cold, stormy nadir between 1560 and 1720, with a three-decade interruption of warmer, more tranquil weather between 1629 and 1662. Newly considered ship logbooks, diaries and other documentary evidence suggest that a rise in the frequency of easterly winds accompanied the coldest phases of the Little Ice Age, and these decadal climatic trends had consequences for regional warfare. Fought between 1652 and 1674, the Anglo-Dutch wars at sea were contested in a period of transition between decade-scale climatic regimes and consequently provide useful case studies into the relationship between meteorological trends and early modern military operations. In the first war, persistent westerly winds born of a warmer climate frequently helped crews aboard larger English warships set the terms of most naval engagements. However, during the second and third wars more frequent easterlies stimulated by a cooler climate granted critical advantages to Dutch fleets that had adopted elements of English tactics and technology. Ultimately, the changing climate of the Little Ice Age must be considered alongside human agency and the political, economic or cultural influences typically examined by military historians to explain the course of early modern warfare.